PENGARUH KEGIATAN MUHADHARAH TERHADAP KECERDASAN EMOSIONAL SANTRI - muhammad Rosyid; Fitriyah (LPPM STAI Darussalam Lampung, 2024)
This research aims to analyze: First, muhadharah activities in the Islamic boarding school environment; level of emotional intelligence of Islamic boarding school students. Second, to find out the influence of muhadharah activities on the emotional intelligence of Islamic boarding school students. This research was conducted at the Roudhotul Qur'an Darul Falah 3 Cukir Jombang Islamic Boarding School. This research uses a quantitative type of research. The sample in this study was 50 active students at the Roudhotul Qur'an Darul Falah 3 Cukir Jombang Islamic Boarding School. The approach used is a case study approach with data analysis techniques using the t-test. The research instruments used were observation, questionnaires and documentation. Research results: first, muhadharah activities are routinely held on Friday nights. Second, the level of emotional intelligence of students is high. Third, there is the influence of muhadharah activities on the emotional intelligence of students.